2019
DOI: 10.1016/j.ipl.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A note on the efficiency of position mechanisms with budget constraints

Abstract: We study the social efficiency of several well-known mechanisms for the allocation of a set of available (advertising) positions to a set of competing budget-constrained users (advertisers). Specifically, we focus on the Generalized Second Price auction (GSP), the Vickrey-Clarke-Groves mechanism (VCG) and the Expressive Generalized First Price auction (EGFP). Using the liquid welfare as our efficiency benchmark, we prove a tight bound of 2 on the liquid price of anarchy and stability of these mechanisms for pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As an e ciency benchmark, liquid welfare has been studied recently in di erent contexts such as in the design of truthful mechanisms (see [Dobzinski and Paes Leme, 2014;Xiao, 2015, 2017]) and in the analysis of combinatorial Walrasian equilibria with budgets [Dughmi et al, 2016]. In the context of the price of anarchy, it was considered recently in simultaneous rst price auctions by Azar et al [2017] and in position auctions by Voudouris [2019]. Caragiannis and Voudouris [2016] were the rst to prove that the liquid price of anarchy of the Kelly mechanism is constant.…”
Section: Lpoamentioning
confidence: 99%
“…As an e ciency benchmark, liquid welfare has been studied recently in di erent contexts such as in the design of truthful mechanisms (see [Dobzinski and Paes Leme, 2014;Xiao, 2015, 2017]) and in the analysis of combinatorial Walrasian equilibria with budgets [Dughmi et al, 2016]. In the context of the price of anarchy, it was considered recently in simultaneous rst price auctions by Azar et al [2017] and in position auctions by Voudouris [2019]. Caragiannis and Voudouris [2016] were the rst to prove that the liquid price of anarchy of the Kelly mechanism is constant.…”
Section: Lpoamentioning
confidence: 99%
“…Following their work, Caragiannis and Voudouris [2018] characterized the structure of worst-case pure equilibria and proved tight bounds on the liquid price of anarchy for almost all divisible resource allocation mechanisms. In a similar spirit, Voudouris [2019] showed tight bounds on the pure liquid price of anarchy and stability for ad auctions, including the generalized second price auction and VCG. Our work is mostly related to that of Azar et al [2017] who showed a constant bound on the liquid price of anarchy of simultaneous first and second price auctions for Bayes-Nash equilibria when the agents have additive valuation functions, and a tight bound of 2 on the liquid price of anarchy for pure equilibria when the agents have fractionallysubadditive valuations.…”
Section: Introductionmentioning
confidence: 87%
“…Following their work, Caragiannis and Voudouris [2018] characterized the structure of worst-case pure equilibria and proved tight bounds on the liquid price of anarchy for almost all divisible resource allocation mechanisms. In a similar spirit, Voudouris [2019] showed tight bounds on the pure liquid price of anarchy and stability for ad auctions, including the generalized second price auction and VCG. Our work is mostly related to that of Azar et al [2017] who showed a constant bound on the liquid price of anarchy of simultaneous first and second price auctions for Bayes-Nash equilibria when the agents have additive valuation functions, and a tight bound of 2 on the liquid price of anarchy for pure equilibria when the agents have fractionallysubadditive valuations.…”
Section: Introductionmentioning
confidence: 87%